Main executive functions that change during normal aging - Flores-Villavicencio, María Elena (2025)
Executive functions are cognitive abilities that associate ideas, movements and actions, facilitate the adaptation of human behavior to different situations, providing solutions to highly complex problems. They are the first functions to suffer a decline in normal aging in older adults, a normal decline is manifested through a general slowing in relation to working memory, verbal abstraction, calculation, logical reasoning and inhibitory mechanisms, increasing the number of incorrect answers. The objective was to evaluate the executive functions that decrease during the normal aging process according to older adult ages. 182 healthy older adults were evaluated, tasks were developed to evaluate the executive functions of working memory and inhibitory control, and they were divided into four age groups. It was demonstrated that, with age, the probability of presenting a greater cognitive decline in old age increases. The older age group presented more difficulty in performing sequencing tasks, working memory similarity and inhibitory control tasks, presenting an increase in the execution time of the responses. Working memory and inhibitory control showed a normal decline, with an increase at older ages.